The Role of Hippocampus in the Pathophysiology of Depression - Özlem Donat Eker; M. Çağdaş Eker (Psikiyatride Güncel Yaklaşımlar, 2009)
Hippocampus, as a part of the limbic cortex, has a variety of functions ranging from mating behavior to memory besides its role in the regulation of emotions. The hippocampus has reciprocal interactions of with other brain regions which act in the pathophysiology of major depressive disorder (MDD). Moreover, since the hippocampus is a scene for the neurogenesis, which can be seen as a response to antidepressant treatment, the hippocampus became a focus of attention in neuroimaging studies of MDD. It has been shown that brain derived neurotrophic factor (BDNF), that is responsible from the neurogenesis, is associated with the response to the antidepressants and antidepressant drugs are ineffective if neurogenesis is hindered.Hippocampal atrophy is expected with the decrease of neurogenesis as a result of the lower BDNF levels with the deleterious effects of glucocorticoids in depression. Recurrent and severe depression seems to cause such a volume reduction though first episode MDD subjects do not differ from healthy individuals in respect to their hippocampal volumes (HCVs) measured by magnetic resonance imaging methods. One may argue regarding these findings that the atrophy in the hippocampus may be observed in the long term and the decrease in BDNF levels may predispose the volume reduction. Although it has been postulated that smaller HCV as a result of genetic and environmental factors and prior to the illness, may cause a vulnerability to MDD, sufficient evidence has not been accumulated yet and the view that HCV loss develops as depression progresses is widely accepted. Findings that serum BDNF (sBDNF) is lower in MDD patients though HCVs of patients do not differ from healthy individuals and the positive correlation of sBDNF with HCV seen only in the patient group support this view. It can be assumed that depressed patients have sensitivity for the fluctuations in BDNF levels. Follow-up studies which consider effects of hipotalamo-pituiter-adrenal axis dysregulation and monoamine systems are needed to further elucidate the role of BDNF in the pathogenesis of MDD. Results of these studies may lead the way for the treatment of resistant or recurrent depressive disorder.